1987
DOI: 10.2135/cropsci1987.0011183x002700060027x
|View full text |Cite
|
Sign up to set email alerts
|

Plant Density Effects on Main Culm and Tiller Development of Grain Sorghum1

Abstract: The development of tillers represent as an important yield compensation mechanism for many cereals. A 2‐yr irrigated field study was conducted at Temple, TX, on a Houston Black clay (fine, montmorillonitic, thermic Udic Pellusterts) using two recently developed low tillering sorghum hybrids [Sorghum bicolor (L.) Moench], ATx623 ✕ RTx430 and ATx378 ✕ RTx430, to compare tiller phenological development to that of the main culm, and determine the impact of tillering on crop phenology and grain yield. Planting date… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…Though optimal plant densities for grain sorghum production differ among geographic regions, research indicates that grain yield generally increases as plant density increases (3,4,5,10,13). At sub‐optimal plant densities grain sorghum head number per plant or seed number per head increased when compared to the recommended plant density (2,4,6,7,10,13). Larson and Vanderlip (8) suggested that grain sorghum's ability to compensate for decreased plant density was related to plant space uniformity.…”
Section: Introductionmentioning
confidence: 92%
“…Though optimal plant densities for grain sorghum production differ among geographic regions, research indicates that grain yield generally increases as plant density increases (3,4,5,10,13). At sub‐optimal plant densities grain sorghum head number per plant or seed number per head increased when compared to the recommended plant density (2,4,6,7,10,13). Larson and Vanderlip (8) suggested that grain sorghum's ability to compensate for decreased plant density was related to plant space uniformity.…”
Section: Introductionmentioning
confidence: 92%
“…Environmental variation in tillering is mainly driven by assimilate availability at the tiller site during the period of tiller production (Friend, 1965;Honda and Okajima, 1970;Kirby and Faris, 1972;Ong and Marshall, 1979;Kirby et al, 1985;Gerik and Neely, 1987). As a complex trait, its phenotypic expression is regulated by the genetic makeup of the variety (G), the growing environment (E), the management practice (M), and their interactions (G ´ E ´ M).…”
Section: Predicting Tillering Of Diverse Sorghum Germplasm Across Envmentioning
confidence: 99%
“…Though a significant part of variation in tillering is under genetic control, there is also significant variation in tillering associated with changed environmental and management conditions. On the other hand, an increase in intercepted radiation enhances tillering through the increase of assimilate availability at the tiller sites (Cannell, 1969;Gerik and Neely, 1987;Neuteboom, 1998a, 1998b;Gautier et al, 1999;Lafarge and Hammer, 2002a;Alam et al, 2014a). Assimilate availability for tillering depends on the balance of the demand by other growth processes and the supply of assimilates during tiller formation (Lafarge et al, 2002).…”
Section: Predicting Tillering Of Diverse Sorghum Germplasm Across Envmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased tillering is also associated with reduced stem size [17]. Temperature and plant density also influence tillering potential [18].…”
Section: Basic Phenological Traits Of Importance In Sorghummentioning
confidence: 99%